2004
DOI: 10.1037/0735-7044.118.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Amygdalar NMDA Receptors Control the Expression of Associative Reflex Facilitation and Three Other Conditional Responses.

Abstract: Four conditional responses (CRs) were measured in rats implanted with bilateral cannulas in the basolateral nuclear complex of the amygdala (BLA). During retention testing in either the original training context or a shifted context, BLA was infused with artificial cerebral spinal fluid (ACSF) or ACSF containing an N-methyl-D-aspartate receptor antagonist (APV). Regardless of the testing context, APV infusion into BLA completely blocked the expression of conditional eyeblink facilitation and significantly atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 74 publications
(217 reference statements)
2
26
0
Order By: Relevance
“…When identically measured, the intensity of the 22 kHz tone was 67 dB. As in our previous studies (Choi et al, 2001;Lindquist and Brown, 2004), the intensity of the 4 kHz tone was 75 dB, measured using the C scale of a digital sound meter (model 33-2055;range, 32-10,000 Hz;Realistic, Fort Worth, TX).…”
Section: Methodsmentioning
confidence: 77%
See 2 more Smart Citations
“…When identically measured, the intensity of the 22 kHz tone was 67 dB. As in our previous studies (Choi et al, 2001;Lindquist and Brown, 2004), the intensity of the 4 kHz tone was 75 dB, measured using the C scale of a digital sound meter (model 33-2055;range, 32-10,000 Hz;Realistic, Fort Worth, TX).…”
Section: Methodsmentioning
confidence: 77%
“…All freezing data were analyzed by the experimenter and a blind assistant, resulting in an interobserver correlation of r ϭ 0.94 (cf. Lindquist and Brown, 2004). The pattern of statistical significance was identical for both, although only freezing scores collected by the blind assistant were used for data analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, involvement of the BLA in decremented learning after stress in females has not been previously demonstrated. Although the BLA is not necessary for eyeblink conditioning, lesions of the BLA profoundly retard acquisition (Neufeld and Mintz, 2001;Lee and Kim, 2004;Lindquist and Brown, 2004), suggesting that the BLA is involved in the modulation of learning during arousing and fearful conditions (Packard and Cahill, 2001;McGaugh, 2004). Inescapable stress elicits fear that generalizes beyond the context in which inescapable stress was conducted, and this fear is evident before US delivery (Maier, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Penick and Solomon (1991) showed that, following conditioning of the nictitating membrane with a puff, a switch in context disrupted substantially the expression of the CR (Penick and Solomon 1991). However, a subsequent study did not replicate these results (Lindquist and Brown 2004). Another study found that the expression of CRs was substantially reduced after postacquisition exposure to the acquisition context relative to a home-cage control condition (Poulos et al 2006).…”
mentioning
confidence: 77%